PENGARUH KONSENTRASI KEPEMILIKAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT - Fais Muta'as Sidiq (2021)
This research is a type of quantitative research that aims to determine the effect of concentration ownership and institutional ownership on sustainability reports disclosure. Sustainability report disclosure in this study was measured by GRI G4 and GRI Standards. The sample of this research was 39 non-financial companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The analysis technique used is multiple linear regression analysis with panel data regression using the STATA version 16 program. The findings of this study reveal that both monitoring and control mechanisms, namely concentrated ownership and institutional ownership would jointly can have a significant influence on management. Although in this case only concentrated ownership can exert influence through an effective monitoring mechanism on management, thereby increasing the disclosure of sustainability reports, while institutional ownership has the opposite effect. In addition, this study has the result that the control variable of firm age has a significant positive effect and leverage has a significant negative effect on sustainability report disclosure. Meanwhile, the profitability and size of the company have no effect on sustainability report disclosure.